2015
DOI: 10.1007/s12012-015-9341-z
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 Ameliorates Cardiac Fibrosis After Myocardial Infarction by Inhibiting the TGF-β1/Smad3 Pathway

Abstract: Notch3 and TGF-β1 signaling play a key role in the pathogenesis and progression of chronic cardiovascular disease. However, whether Notch3 protects against myocardial infarction (MI) and the underlying mechanisms remains unknown. C57BL/6 mice were randomized to be treated with Notch3 siRNA (siNotch3) or lentivirus carrying Notch3 cDNA (Notch3) before coronary artery ligation. Four weeks after constructing MI model, cardiac function and fibrosis were compared between groups. The cardiac fibroblast cells (CFs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…Furthermore, Nemir et al showed that Notch activation in the stressed heart of adult mice inhibited TGF‐β1 induced CMT and cardiac fibrosis (Nemir et al, ). In addition, lentivirus‐mediated Notch3 overexpression inhibited CMT of TGF‐β1‐treated cardiac fibroblasts and ameliorated cardiac fibrosis in MI mice (Zhang et al, ). Consistent with recent studies, our results demonstrated that activated Notch signaling could inhibit TGF‐β1/Smad3 signaling mediated CMT in CFs and reduce myocardial fibrosis in MI rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nemir et al showed that Notch activation in the stressed heart of adult mice inhibited TGF‐β1 induced CMT and cardiac fibrosis (Nemir et al, ). In addition, lentivirus‐mediated Notch3 overexpression inhibited CMT of TGF‐β1‐treated cardiac fibroblasts and ameliorated cardiac fibrosis in MI mice (Zhang et al, ). Consistent with recent studies, our results demonstrated that activated Notch signaling could inhibit TGF‐β1/Smad3 signaling mediated CMT in CFs and reduce myocardial fibrosis in MI rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction model was established in male Sprague‐Dawley (SD) rats using left anterior descending coronary artery (LAD) ligation method as described previously . The rats were anesthetized with sodium pentobarbital (60 mg/kg, ip) and a thoracotomy was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in vivo intramyocardial delivery of hydrogels containing the Notch1 ligand Jagged-1 in rats with MI reduced cardiac fibrosis (Boopathy et al, 2015). Moreover, augmentation of Notch3 expression by lentiviral transfection inhibited fibroblast–myofibroblast transition both in TGF-β1-treated cardiac fibroblasts in vitro and in mice with MI, minimizing cardiac fibrosis (Zhang et al, 2016). As previously mentioned, Notch signaling can inhibit EMT (Zhou et al, 2015; Hu and Phan, 2016), which also contributes to cardiac fibrosis (von Gise and Pu, 2012).…”
Section: Notch Pathway In Cardiac Fibrosismentioning
confidence: 99%
“…The main identified mechanism by which Notch signaling interferes with myofibroblast differentiation consists in its ability to antagonize TGF-β/Smad3 signaling, the key intracellular pathway promoting cell activation and fibrogenesis (Zhang et al, 2016; Travers et al, 2016) ( Figure 2 ).…”
Section: Notch Pathway In Cardiac Fibrosismentioning
confidence: 99%